2020
DOI: 10.26911/theijmed.2020.05.03.01
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Slow Stroke Back Massage and Lavender Aromatherapy on Blood Pressure in Hypertensive Patients

Abstract: Background: Elderly is an age group which is extremely susceptible to suffer from health problems such as hypertension. Hypertension among the elderly is instigated by structural and functional changes in blood vessels. The changes include atherosclerosis, loss of connective tissue elasticity, and decreased vascular muscle relaxation that it reduces the distension and tensile strength of blood vessels. One of the therapies that may be implemented to elderly with hypertension is slow stroke back massage (SSBM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
2
0
0
1
Order By: Relevance
“…therapy. These results are in line with research bySani and Irdianty (2020) which shows the mean difference between Systolic Blood Pressure (TDS) and Diastolic Blood Pressure (TDD) before and after SSBM intervention, namely the previous mean TDS was 167.80 to 133.63 after the intervention. TDD before the intervention showed a value of 68.88 and after the SSBM intervention it became 68.28.…”
supporting
confidence: 91%
“…therapy. These results are in line with research bySani and Irdianty (2020) which shows the mean difference between Systolic Blood Pressure (TDS) and Diastolic Blood Pressure (TDD) before and after SSBM intervention, namely the previous mean TDS was 167.80 to 133.63 after the intervention. TDD before the intervention showed a value of 68.88 and after the SSBM intervention it became 68.28.…”
supporting
confidence: 91%
“…These results are in line with research conducted by (Wahyuni et al, 2020) that the dose of effleurage massage given is quite effective within 20 minutes at each meeting so that it is able to induce all body adaptation processes, strengthen the respiratory and cardiovascular systems, increase parasympathetic activity so that (Mohebbi et al, 2014) reduces systolic and diastolic blood pressure. This result is also supported by the research of Kusumarini et al (2015) which found that effleurage massage which consists of several movements and repetitions in a certain time will be able to effectively reduce systolic and diastolic blood pressure (Sani et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Terapi relaksasi merupakan salah satu teknik untuk mengurangi stres dan ketegangan pada otot. Terapi relaksasi diperlukan pada penderita hipertensi agar membuat pembuluh darah menjadi rileks sehingga akan terjadi vasodilatasi yang menyebabkan tekanan darah kembali normal Sani (2020). Penelitian ini didukung oleh Tarigan (2014), menyatakan bahwa salah satu cara terbaik untuk menurunkan tekanan darah adalah dengan terapi pijat.…”
Section: Pengaruh Terapi Pijat Refleksi Kaki Terhadap Tekanan Darah P...unclassified